The High Representative and EU Foreign Policy Integration A Comparative Study of Kosovo and Ukraine - Amadio Viceré, Maria Giulia (European Administrative Governance,, 2018)
Adopting a broad conceptualization of foreign and security policy, the book examines the role of the High Representative as chair of the Foreign Affairs Council and in her/his capacity as Vice President of the European Commission to assess different patterns of integrated efforts in EU foreign and security policies. In this way, it presents a new perspective from which institutional practices in this specific area can be examined. This contribution is particularly valuable for scholars and students of EU foreign and security policy; of external relations of the EU; of international relations more in general; and of EU integration and politics. At the same time, the book contributes to the empirical understanding of two EU policies that have recently been at the centre of the debate among scholars, policy analysts and practitioners, namely the EU enlargement towards the Western Balkans and the EU Neighborhood Policy and Eastern Partnership. Maria Giulia Amadio Viceré is an Assistant Professor at the University of Leiden. Before that, she has been a Visiting Research Associate at the Policy Institute at King's College, an elected member of the UACES Student Forum, a Blue Book Trainee at the European Commission and a research trainee at the European Policy Centre.